A study of the attitudes of physical education and sports students towards the profession of sports management - belboul, moussa (sports creativity, 2025)
The management profession in general attracts many university graduates in all disciplines, such as the physical education and sports specialization, which deals with various fields related to managing bodies and federations, and managing sports facilities, clubs, associations, and sports teams, especially in light of the market economy that focuses on quality. Students specializing in sports management and administration in every society are considered the active force that plays a prominent role in the processes of change and innovation, and a reservoir of future leaders in the administrative sense. Many sports institutions hope that their role will inevitably be in serving society and its development if they are prepared educationally and according to scientific foundations and developmental programs to achieve general goals.